Global supply chains at work in Central and Eastern European Countries: Impact of FDI on export restructuring and productivity growth - Joéze Damijan; éCrt Kostevc; Matija Rojec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
This paper empirically accounts for the importance of the 'global supply chains' concept for export restructuring and productivity growth in Central and Eastern European Countries (CEECs) in the period 1995-2007. Using industry-level data and accounting for technology intensity, we show that FDI has significantly contributed to export restructuring in the CEECs. The effects of FDI are, however, heterogenous across countries. While more advanced core CEECs succeeded in boosting exports in higher-end technology industries, non-core CEECs stuck with export specialization in lower-end technology industries. This suggests that where FDI flows have been directed is of key importance. Our results show that export restructuring and economic specialization brought about by FDI during the last two decades in the CEECs might matter a lot for their potential for long-run productivity growth. Industries of higher-end technology intensity have experienced substantially higher productivity growth and so have countries more successful in attracting FDI to these industries.
Keywords: F210; F230; L600; O140; 330; Lieferkette; Direktinvestition; Internationale Wirtschaft; Produktivität; Osteuropa